Energy harvesting efficiency in GaN nanowire-based nanogenerators: the critical influence of the Schottky nanocontact. Issue 13 (21st March 2017) - Jamond, Nicolas; Chrétien, Pascal; Gatilova, Lina; Galopin, Elisabeth; Travers, Laurent; Harmand, Jean-Christophe; Glas, Frank; Houzé, Frédéric; Gogneau, Noëlle
Abstract : Harvesting efficiency of piezoelectric energy generated by GaN nanowires is strongly affected by Schottky nanocontact properties at the interface with the electrode. Abstract : The performances of 1D-nanostructure based nanogenerators are governed by the ability of nanostructures to efficiently convert mechanical deformation into electrical energy, and by the efficiency with which this piezo-generated energy is harvested. In this paper, we highlight the crucial influence of the GaN nanowire–metal Schottky nanocontact on the energy harvesting efficiency. Three different metals, p-type doped diamond, PtSi and Pt/Ir, have been investigated. By using an atomic force microscope equipped with a Resiscope module, we demonstrate that the harvesting of piezo-generated energy is up to 2.4 times more efficient using a platinum-based Schottky nanocontact compared to a doped diamond-based nanocontact. In light of Schottky contact characteristics, we evidence that the conventional description of the Schottky diode cannot be applied. The contact is governed by its nanometer size. This specific behaviour induces notably a lowering of the Schottky barrier height, which gives rise to an enhanced conduction. We especially demonstrate that this effective thinning is directly correlated with the improvement of the energy harvesting efficiency, which is much pronounced for Pt-based Schottky diodes. These results constitute a building block to the overall improvement of NW-based nanogenerator devices.